Attitude and Behaviour Intention of Muslim Z Generation to Save in Islamic Banks: The Role of Knowledge and Religiosity - Purwanto, Purwanto; Dasuki, Ali Ibrahim; Ghofur, Abdul; Abdullah, Shodiq (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2022)
This study aims to investigate the impact of knowledge and religiosity on attitudes toward Islamic banks and the saving intentions of Generation Z Muslims. Data were collected using a convenience sampling method from students at Islamic higher education institutions in Central Java, Indonesia. A total of 210 respondents aged 17-27 participated in the study. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that both knowledge and religiosity significantly shape attitudes toward Islamic banks among Generation Z Muslims. Knowledge emerged as the most influential factor shaping attitudes. Attitudes, in turn, significantly influence the saving intentions of Generation Z Muslims at Islamic banks. This study further demonstrates that attitudes are the strongest determinant of the saving intentions of Generation Z Muslims at Islamic banks. Practically, this research provides valuable insights for Islamic bank marketers in formulating strategies to attract Generation Z Muslims to save in Islamic banks. Theoretically, this study affirms the importance of integrating cognitive, affective, and spiritual dimensions in consumer behavior analysis to better understand and predict behavior.